2016
DOI: 10.3390/min6030059
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Composition and Temperature on the Conductivity of Synthetic Copper Electrorefining Electrolyte

Abstract: Abstract:The physico-chemical properties of the copper electrolyte significantly affect the energy consumption of the electrorefining process and the quality of the cathode product. Favorable conditions for electrorefining processes are typically achieved by keeping both the electrolyte conductivity and diffusion coefficient of Cu(II) high, while ensuring low electrolyte viscosity. In this work the conductivity of the copper electrorefining electrolyte was investigated as a function of temperature (50-70˝C) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…According to Aalto-I, increases in both temperature and H 2 SO 4 have a positive effect on conductivity, whereas the presence of metal ions (Zn, Mn, Mg) has a negative impact on solution conductivity. These findings are in agreement with earlier studies of Zn electrowinning conductivity [15,[24][25][26], and are similar to the behavior found for Cu, Ni, and As, in copper electrowinning electrolytes [22].…”
Section: Comparison Of Models With Synthetic Solutionssupporting
confidence: 92%
See 2 more Smart Citations
“…According to Aalto-I, increases in both temperature and H 2 SO 4 have a positive effect on conductivity, whereas the presence of metal ions (Zn, Mn, Mg) has a negative impact on solution conductivity. These findings are in agreement with earlier studies of Zn electrowinning conductivity [15,[24][25][26], and are similar to the behavior found for Cu, Ni, and As, in copper electrowinning electrolytes [22].…”
Section: Comparison Of Models With Synthetic Solutionssupporting
confidence: 92%
“…According to Aalto-I, increases in both temperature and H2SO4 have a positive effect on conductivity, whereas the presence of metal ions (Zn, Mn, Mg) has a negative impact on solution conductivity. These findings are in agreement with earlier studies of Zn electrowinning conductivity [15,[24][25][26], and are similar to the behavior found for Cu, Ni, and As, in copper electrowinning electrolytes [22]. From Figure 3, it can be seen that model Aalto-I clearly has valid coefficients throughout the parameters tested, whereas Aalto-II shows that there are valid correlations between both Zn and H 2 SO 4 with temperature.…”
Section: Aalto Conductivity Modelssupporting
confidence: 91%
See 1 more Smart Citation
“…A majority of the nickel dissolves into the electrolyte, increasing the resistivity of the electrolyte. Consequently, this increases the electricity consumption of the process [2,5]. In the anode, nickel exists primarily as NiO and kupferglimmer [3], and it has been suggested that nickel increases the porosity of the slime layer on the anode surface and causes a layered structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the electrical conductivity and the economic price of lead alloys, a continuous protective layer of lead dioxide is formed on the surface of the anode that is sufficiently conductive for circuit requirements and has the advantage of improving the corrosion resistance of the anode [3][4][5][6]. Since the introduction of the electro-winning technique into commercial use to produce copper, in the middle of the 19 th century [7], many improvements have been introduced to both the corrosion resistance and mechanical properties of lead anodes. Cast anodes were replaced by rolled anodes and antimonial alloys were superseded by calcium additions to the lead to increase the strength of the anode, while tin was found to have a beneficial effect on improving corrosion resistance, conductivity and oxygen evolution [4].…”
Section: Introductionmentioning
confidence: 99%